Anti-Mullerian Hormone and Follicle Stimulating Hormone as Markers of Ovarian Agingin a Sample of Iraqi Women - E. Ahmed, Reyam; Al-lami, Makarim Q. (Iraqi Journal of Science, 2022)
One-hundred and twenty Iraqi women (60 single women and 60 married women) with age ranges from (17-49) years have been involved in this study to estimate the levels of anti-mullerian hormone (AMH) and follicle stimulating hormone (FSH) as markers of ovarian aging. The descriptive data [age, body mass index (BMI), age at menarche, duration of menarche] have been recorded. Blood samples were collected from the studied women to determine the levels of AMH and FSH.The results revealed non-significant (p>0.05) differences in levels of AMH and FSH between single women and married women. A significant negative correlation was observed between AMH levels and age in single women (r=-0.519, p<0.05) and married women (r=-0.433, p<0.05). A non-significant correlation was found between AMH levels and BMI in single women, while a significantnegative correlation was found in married women (r=-0.311,p<0.05). A non-significant correlation was observed between AMH levels and age of menarche in the two groups, whilea significant negative correlation was observed between AMH levels and duration of menarche in single women (r= -0.520, p<0.05) and married women (r= -0.396, p<0.05). The results showed a significant positive correlation between FSH levels and age in single women (r= 0.525, p<0.05) and married women (r= 0.346, p<0.05),while asignificant positive correlation was found with BMI (r= 0.315, p<0.05) in single women only. Non-significant correlation was found with age at menarche in studied women, whilea significant positive correlation was noticed with duration of menarche in single women (r= 0.529, p>0.05) and married women (r= 0.339, p>0.05). The correlation between AMH and FSH levels in studied women revealed a significant negative correlation in single women (r=-0.429, p<0.05), while a non-significant correlation was found in married women. In single and married women, a significant (p<0.05) decrease was found in AMH levels; while a significant (p<0.05) increase was found in FSH levels in (≥40 years) age category compared with the other age categories. In single women, non-significant (p>0.05) differences were found in AMH levels among the BMI categories,while a significant (p<0.05) decrease was found in FSH levels in (18.5-24.9 kg/m2) BMI category compared with other BMI categories. In married women, non-significant (p>0.05) differences were found in AMH and FSH levels between the BMI categories.In conclusion,this study demonstrated the importance of measurement of AMH and FSH as a good marker of ovarian aging in Iraqi women.